Pendampingan Digitalisasi Data Transaksi Kolektor pada Koperasi Simpan Pinjam Maju Mapan Jaya Denpasar - I Wayan Widi Karsana; Putu Andhika Kurniawijaya (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Koperasi Simpan Pinjam (KSP) Maju Mapan Jaya is one of the cooperatives engaged in savings and loans. In an effort to provide maximum service to customers, KSP Maju Mapan Jaya has collectors who are tasked with collecting credit installments and taking customer savings deposits directly to the customer's location for the convenience and security of customer funds.Transaction recording is still done manually by cooperative collectors by recording in the savings ledger or loan ledger and then submitting it to the cooperative office. Partners expect assistance in the application of information technology, especially the digitization of collector transaction data to minimize obstacles in the field. The purpose of this community service activity is to help partners provide assistance and implement a digital-based collector transaction data information system.